Perkembangan Bahasa Gaul Remaja Milenial Dalam Media Sosial - Fredin Samohouni Zai; Maria C. A. Sihite (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Languange holds a significant role in facilitating human thinking, serving as a foundation for understanding and accessing knowledge. However, the development of Indonesian language is currently experiencing a decline, mainly due to the widespread influence of social media. Social media users, often referred to as netizens, often use terms or vocabulary that are not in line with linguistic norms. This results in the communication patterns of Indonesian people in daily life, both in oral and written forms. This study uses an observation method with reading and note-taking techniques to describe the development of slang used by millennial teenagers on various social media platforms. The research findings show that the slang used by millennial teenagers comes from various sources, including regional languages, Indonesian, foreign languages, and a combination of Indonesian and foreign languages. Therefore, the use of slang by millennial teenagers is interpreted as a form of self-expression when building friendships and fostering close relationships between fellow teenagers